MicroRNAs and Periodontal Disease: Helpful Therapeutic Targets? - Abdolhakim Palideh; Mostafa Vaghari-Tabari; Ali Nosrati Andevari; Durdi Qujeq; Zatollah Asemi; Forough Alemi; Hemmatollah Rouhani Otaghsara; Sona Rafieyan; Bahman Yousefi (Tabriz University of Medical Sciences, 2023)
Periodontal disease is the most common oral disease. This disease can be considered as an inflammatory disease. The immune response to bacteria accumulated in the gum line plays a key role in the pathogenesis of periodontal disease. In addition to immune cells, periodontal ligament cells and gingival epithelial cells are also involved in the pathogenesis of this disease. miRNAs which are small RNA molecules with around 22 nucleotides have a considerable relationship with the immune system affecting a wide range of immunological events. These small molecules are also in relation with periodontium tissues especially periodontal ligament cells. Extensive studies have been performed in recent years on the role of miRNAs in the pathogenesis of periodontal disease. In this review paper, we have reviewed the results of these studies and discussed the role of miRNAs in the immunopathogenesis of periodontal disease comprehensively. miRNAs play an important role in the pathogenesis of periodontal disease and maybe helpful therapeutic targets for the treatment of periodontal disease.